Developing e-cookies business model / Surianty Mohd Sopian - Mohd Sopian, Surianty (2010)
The idea for this research on developing e-Cookies business models emerged when ebusiness, e-commerce and the so called new economy were blooming and booming. This research was prepared according to the elements and design which related to business model of e-Cookies. There are a lot of cookies websites in Malaysia, but it still not convenience enough to the users in order to buy the cookies online. The ordering process takes so much time to interact with customers and most bakers have a small marketing budget to advertise their products and services in a local region. The objectives of this research are identifying the elements for bakery business and developing the prototype to demonstrate business model of e-Cookies. To achieve objectives; survey, interview and observe the existing cookies websites were being done. As a result, the elements of e- Cookies are value proposition, relationship, distribution channel, activity, capability, cost structure, and revenue flows. This research concludes that, the e-Cookies is the alternative way in promoting the products to users in order to enlarge market segment in cookies business industry.